Anomalous origin of left coronary arteries from the pulmonary artery in an asymptomatic adult: An autopsy case report. Issue 38 (September 2019) - Al Shaarani, Majd; Alzubaidi, Yasir; Jin, Long
Abstract: Rationale: Anomalous Origin of Left Coronary Arteries from the Pulmonary Artery (ALCAPA), also known as Bland-White-Garland (BWG), is a rare form of coronary artery anomaly that is usually discovered in the first few months of life. Only rarely can patients with this anomaly reach adulthood without symptoms. Patient concerns: A 28-year-old female was witnessed suddenly collapse with a seizure-like episode by her colleagues at work. Diagnosis and Intervention: Routine cardiopulmonary resuscitation was performed by emergency medical service technologists. The patient was unable to be revived. Postmortem examination revealed the patient had ALCAPA with a focal chronic ischemic injury of the left ventricle. Moreover, a high take-off of the right coronary artery was also discovered. Outcomes: The patient passed away due to ALCAPA. The mechanism of death was cardiac arrhythmia being triggered by myocardial ischemic changes. Lessons: In the rare cases where ALCAPA manifests in an asymptomatic adult, the mortality rate is very high. This case demonstrates the importance of awareness of such patients living under the tremendous risk of sudden cardiac death.